Acute Kidney Injury in Intensive Care Unit: A Clinical and Outcome Study - Narinder Pal Singh; Danish Kathuria; Neeru P. Aggarwal; Anish Kumar Gupta; Gurleen Kaur (Indian Journal of Medical Specialities)
Background: Acute kidney injury (AKI) has both short term as well as long-term consequences in critically ill patients. The present study is an attempt to study its etiological profile in intensive care units (ICUs) which has been only scarcely done in India. Methods: One hundred and twenty patients admitted with or developing AKI during their ICU stay were included in the prospective study and were defined as well as staged according to the Kidney Disease: Improving Global Outcomes (KDIGO) guidelines. Patients were followed up at discharge and at 3 months to determine the outcome as either favorable (renal recovery) or adverse (residual renal dysfunction, dialysis dependence, or death). Various known risk factors, as laid down by KDIGO, were identified and analyzed with respect to their association with the outcome. Results: Out of total of 120 subjects, almost half of the subjects (47.5%) had Stage I AKI, 27.5% had Stage II AKI and the remaining quarter of subjects had Stage III AKI. One fourth had pre-existing chronic kidney disease and three-fourth subjects had developed de novo AKI of which more than half of patients had community-acquired AKI. Anemia and sepsis were the most prevalent risk factors. The highest rate of renal recovery was demonstrated in Stage I AKI. Overall mortality was 28%, highest in Stage III AKI. Conclusion: The study demonstrated increasing prevalence of the adverse outcome in a linear fashion with an increase in the severity of AKI. Sepsis was not only the most prevalent risk factor but was also strongly associated with an adverse outcome. The epidemiology of AKI in critical care in India has started to resemble high-income group countries, in terms of both age distribution as well as etiology.